BIOFEEDBACK: A NEW METHOD FOR CORRECTION OF MOTOR DISORDERS IN PATIENTS WITH MULTIPLE SCLEROSIS - Ya. S. Pekker; V. M. Alifirova; N. G. Brazovskaya; A. A. Ryazantseva; A. N. Pribylskaya (Бюллетень сибирской медицины)
Major disabling factors in multiple sclerosis is motor disorders. Rehabilitation of such violations is one of the most important medical and social problems. Currently, most of the role given to the development of methods for correction of motor disorders based on accessing natural resources of the human body. One of these methods is the adaptive control with biofeedback (BFB). The aim of our study was the correction of motor disorders in multiple sclerosis patients using biofeedback training. In the study, we have developed scenarios for training rehabilitation program computer EMG biofeedback aimed at correction of motor disorders in patients with multiple sclerosis (MS). The method was tested in the neurological clinic of SSMU. The study included 9 patients with definite diagnosis of MS with the presence of the clinical picture of combined pyramidal and cerebellar symptoms. Assessed the effectiveness of rehabilitation procedures biofeedback training using specialized scales (rating scale functional systems Kurtzke; questionnaire research quality of life – SF-36, evaluation of disease impact Profile – SIP and score on a scale fatigue – FSS). In the studied group of patients decreased score on a scale of fatigue (FSS), increased motor control (SIP2), the physical and mental components of health (SF-36). The tendency to reduce the amount of neurological deficit by reducing the points on the pyramidal Kurtske violations. Analysis of the exchange rate dynamics of biofeedback training on EMG for trained muscles indicates an increase in the recorded signal OEMG from session to session. Proved a tendency to increase strength and coordination trained muscles of patients studied.Positive results of biofeedback therapy in patients with MS can be recommended to use this method in the complex rehabilitation measures to correct motor and psycho-emotional disorders.